The Effect of REACT Learning Strategy Assisted Structured Worksheet on Mathematical Problem-Solving Ability - Ratna Juwita; Dwi Antari Wijayanti; Leny Dhianti Haeruman (Jurnal Inovasi Matematika, 2024)
This research aims to determine the effect of the REACT learning strategy assisted by structured student worksheets on mathematical problem-solving ability. This study design employs a quasi-experiment with a posttest-only control group design. The sampling technique was carried out using purposive sampling and cluster random sampling. Students from classes X7 and X9 at SMA Negeri 3 Karawang were used for the research samples. The instrument in this research consisted of four description questions on linear program material that had been tested for validity and reliability. The results of hypothesis testing with an independent sample test (t-test) at the 5% significance level show that there is an effect of the implementation of the REACT learning strategy assisted by structured student worksheet on mathematical problem-solving ability